2019
DOI: 10.1177/1074248419858113
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Ranolazine on Reentrant Ventricular Arrhythmias Induced After Subacute Myocardial Infarction in Rabbits

Abstract: Ranolazine has been found to prevent ventricular arrhythmias (VAs) during acute myocardial infarction (AMI). This study aimed to investigate its efficacy on VAs induced several days post-MI. For this purpose, 13 anesthetized rabbits underwent coronary artery ligation. Ten of these animals that survived AMI were reanesthetized 3 to 7 days later for electrophysiologic testing. An endocardial monophasic action potential combination catheter was placed in the right ventricle for simultaneous pacing and recording. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this respect, it has been shown that the higher dose of ranolazine has antiarrhythmic effects, while the lower one seems to be ineffective or even proarrhythmic. The uthors supposed that the mechanism by which the ranolazine exerts its beneficial effects could be related to a significant increase in ventricular refractoriness possibly secondary to the IKr blockade [68].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…In this respect, it has been shown that the higher dose of ranolazine has antiarrhythmic effects, while the lower one seems to be ineffective or even proarrhythmic. The uthors supposed that the mechanism by which the ranolazine exerts its beneficial effects could be related to a significant increase in ventricular refractoriness possibly secondary to the IKr blockade [68].…”
Section: Arrhythmiasmentioning
confidence: 99%